PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA PADA MATERI INDONESIAKU KAYA BUDAYA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SDS IT NURUL IKHWAN - Aulia, Aulia Putri; Muhammad Noer Fadlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop diorama-based instructional media on the topic "MyIndonesia is Rich in Culture" to enhance the learning motivation of fourth-gradestudents at SDS IT Nurul Ikhwan. The research was conducted due to the lowlearning motivation among students, which was caused by the use of basic teachingmethods such as lectures and the lack of media utilization in the learning process.The method used is Research and Development (R&D) with the ADDIE model,consisting of five stages: Analysis, Design, Development, Implementation, andEvaluation. The subjects of the study were 20 fourth-grade students, with theinvolvement of subject matter experts and media experts for validation. Thevalidation results showed that the media was highly feasible, with a score of 90%from the subject expert and 87.5% from the media expert. The teacher's responsereached 92%, and the students’ response was 89%. The average student motivationscore increased from 66.55 to 85.15 after using the media, showing an improvementof 27.98%. This increase occurred across all motivational aspects based onMaslow’s theory. The diorama-based learning media proved to be effective inpresenting cultural content in a visual, engaging, and enjoyable way, andsignificantly improved students’ learning motivation.